FRI0560 Intra-Articular Injections with Triamcinolone Hexacetonide in A Cohort of Juvenile Idiopathic Arthritis Patients: Factors Associated with A Good Response. (10th June 2014) - Miotto e Silva, V.B.; Cunha, A.L.G.; Osaku, F.; Len, C.; Furtado, R.; Natour, J.; Terreri, M.T.
Abstract : Background: The intra-articular steroids injections (IASI) for treatment of juvenile idiopathic arthritis (JIA) patients are being increasingly used in pediatric rheumatology. Objectives: To describe and to assess the factors associated with good response to IASI in JIA patients. Methods: A study of JIA patients who were administered IASI with a minimum follow-up of six months was performed between January 2008 and December 2012. The response to IASI regarding the patients was classified as a good response (complete - all joints remained inactive for at least six months or partial - part of the joints remained inactive for at least six months) or poor response (all joints remained active or reactivated in less than six months). The response to IASI regarding the joints was classified as a good response (the joints remained inactive for at least six months) or poor response (the joints remained active or reactivated in less than six months). Results: A total of 165 IASI were administered to 88 patients. Of the 88 JIA patients, 66 were female, 35.2% were persistent oligoarticular, 19.3% extended oligoarticular, 38.6% polyarticular, 4.5% systemic and 2.2% others. Patients were grouped according to disease course in oligoarticular (37.5%), polyarticular (58%) and systemic (4.5%). The mean age at diagnosis was 6.8±4 years and the mean follow-up time was 7.0±4 years. Sixty-two patients (70.4%) showed good response to IASI, 44.3% complete and 26.1% partial. There were no associations between the responses to the IASI and gender (p=0.42), JIA subtype (p=0.07), disease course (p=0.08), antinuclear antibodies (p=0.12), rheumatoid factor (p=0.27), time to diagnosis (p=0.73) and mean follow-up time (p=0.08). There was an association between good response to IASI and presence of uveitis (p=0.01) and earlier age of diagnosis (p=0.03). From the 165 joints injected, there were 100 knees, 30 ankles, 15 wrists, 9 elbows and 11 others. A hundred and four joints (63%) showed good response to IASI, with mean duration of 18.1±13 months. There were no associations between the responses to the IASI and the severity of joint effusion (p=0.49), use of DMARDs (p=0.31) or oral steroids (p=0.55), time of follow-up until the IASI (p=0.25), age at IASI (p=0.53), CHAQ (p=0.53), C reactive protein (p=0.22), erythrocyte sedimentation rate (p=0.41) and number of active (p=0.09) and limited (p=0.77) joints at the time of IASI. There was an association between good response to IASI and the injected joint (p=0.001) - knees, wrists and elbows, the use of ultrasonography to guide the IASI (p=0.02) and the parents and physician visual analogue scale (p=0.01). Local adverse events occurred in nine (0.05%) IASI (five atrophy and four hypochromia). Conclusions: More than half joints showed good response to IASI, with sustained response. The JIA patients with uveitis and earlier age of diagnosis had a good response to IASI. The knees, wrists and elbows were the joints that had the better response with the injections. References: See Y. Ann Acad Med Singapore 1998, 27:105-11. Marti P et al. Eur J Pediatr 2008, 167:425-30. Papadopoulou C et al. Arthritis Care Res 2013, 65:1112-20. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2279